A Novel Diagnostic Method for Invasive Fungal Disease Using the Factor G Alpha Subunit From Limulus polyphemus - Cui, Fang; Luo, Peng; Bai, Yao; Meng, Jiangping (Frontiers in Microbiology, 2021)
Deaths due to invasive fungal disease (IFD) have been increasing every year. Early and rapid detection is important to reduce the mortality rate associated with IFD. In this study, we explored a novel diagnostic method for detecting IFD, which involves the G Factor α subunit (GFαSub) from Limulus polyphemus. The GFαSub double-sandwich method was developed to detect (1,3)-β-D-glucans in human serum using purified GFαSub and horseradish peroxidase-labeled GFαSub. The GFαSub double-sandwich method and the G test were performed and compared. Using GFαSub sequence analysis, the expression plasmid pET30a-GFαSub252-668 was synthesized, and GFαSub252-668 was expressed and purified via isopropyl-β-d-thiogalactoside induction and nickel-nitrilotriacetic acid affinity. The optimization method was established via the orthogonal method. Using this method, the sera of 36 patients with IFD and 92 volunteers without IFD underwent detection, and the receiver operating characteristic curve of the GFαSub252-668 double-sandwich method was described. The sensitivity and specificity of the GFαSub252-668 double-sandwich method were 91.67% and 82.61%, respectively, and there was good correlation with the G test for the serum specimens of 36 patients with pulmonary IFD (R2 = 0.7592). In conclusion, our study suggests that the GFαSub252-668 double-sandwich method was satisfactory at detecting IFD cases. This method can be promoted and further developed as a novel method for diagnosing IFD.